Implementasi Rating ESG dan Kebijakan Dividen terhadap Return Saham - Aditya, Muhammad (Universitas Darwan Ali, 2022)
The purpose of this study is to examine the effect of ESG rating and dividend policy, while PER, and market capitalization as control variables on stock returns in the period 15 September 2021 to 15 March 2022. The sample of this study is all companies listed in the ESGLeaders30 index30. This study uses multiple regression analysis using Eviews 9. The results of this study indicate that the ESG rating and dividend policy do not have a significant effect on stock returns, this is because there are other factors that affect stock returns such as company fundamentals, microeconomics, macroeconomics, and conditions. Covid-19. Meanwhile, dividend policy has a significant positive effect on stock returns.